Development of drive cycles and measurement of fuel consumption of light duty vehicles in Metro Manila - Abaya, Ernesto B. (College of Engineering, University of the Philippines Diliman, 2015)
The urban drive cycles for five different light duty vehicles (LDV) are developed in this study. Furthermore, the fule consumption factors for each of the type of LDV are estimated. The study presents the methodology in the development of the drive cycles in which the speed profiles of the specific type of vehicle is surveyed, downloaded and processed. In the survey of speed data, a Global Positioning System (GPS) device is used as an on- board instrument. The GPS device is placed on the dashboard of every surveyed vehicle and it recorded instantaneous speed in its memory. The speed data is downloaded from the device using software provided by the maker of the device (Garmin) called Mapsource. The speed data is processed using a program to execute the methodology in generating candidate drive cycle. The program creates drive cycle by randomly appending micro trips to form a minimum of twenty minute speed time profile. Furthermore, along with the generated drive cycle. The program also indicated how it compared with the target drive cycle by computing their individual absolute value difference of their joint speed-acceleration probability distribution.Ten drive cycles for each type of LDV are developed which have absolute less than 20%. The final drive cycle is selected from the ten (10) candidate drive cycle developed from each type of LDV. The selected drive cycles are then used in the Vehicle Research and Testing Laboratory at UP College of Engineering, Mechanical Engineering Department to estimate the fuel consumption factors of each type of light duty vehicle considered. The developed drive cycles for the different types of light duty vehicles, namely (1) private cars, (2) taxis, (3) public utility jeepneys, (4) UV express, and (5) light duty duty trucks have average speeds of 17.97 kph, 13.57 kph, 8.43 kph respectively.The fuel consumption factors estimated for all the light duty vehicles tested in the chassis dynamometer laboratory ranges from 3 to 12 km/liter.